Generation-Z Preservice Biology Teachers' Beliefs in Using Technology in Their Future Classroom - Ahmad Kamal Sudrajat; Dita Purwinda Anggrella; Ahmad Iskak Nugroho; Zainudin bin Hassan (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2026)
Technology integration has become an important priority in education, particularly in preparing future teachers to use digital tools effectively in classroom practice. Limited attention, however, has been given to how Generation Z preservice biology teachers perceive technology integration in their future teaching. This study aimed to investigate their beliefs about using technology in biology learning, with particular attention to perceived benefits, functional roles of technology, external influences, and gender differences. A quantitative survey design was employed using a Likert-scale questionnaire. Data were collected from 94 final-semester preservice biology teachers at two public state universities in Indonesia. The data were analyzed using descriptive and inferential statistics to examine patterns of beliefs and differences by gender. The findings showed that male participants reported slightly higher average technological proficiency than female participants, although the difference was not statistically significant. Student engagement emerged as the most influential factor shaping preservice teachers’ beliefs about using technology, followed by the function of technology and external factors. No significant gender differences were found across these three factors. These findings suggest that Generation Z preservice biology teachers, regardless of gender, demonstrate comparable readiness to integrate technology into biology learning. Implications of the study indicate that teacher education programs should prioritize the development of advanced technology-integration competencies and provide training that emphasizes pedagogical readiness rather than gender-based differentiation